P25 Swallowing safety and performance in patients with idiopathic pulmonary fibrosis: Evidence from the water swallow test. (11th November 2022) - Alamer, A; Patterson, J; Drinnan, M; Forrest, I; Ward, C
Abstract : Introduction: Awareness of swallowing abnormalities in respiratory conditions such as (COPD) is growing. However, research into swallowing dysfunction in IPF is limited. Aim: Explore the swallowing safety and performance of the Water Swallow Test (WST) in patients with IPF. Methods: Thirty-four IPF patients were recruited from pulmonary fibrosis support groups around the UK or from the Newcastle Interstitial Lung Disease (ILD) clinic between January and October 2021. The WST was conducted via teleconference call or face-to-face in the ILD clinic. Patients took three volumes of water: 5 mL single-sip, 10 mL single-sip and 100 mL consecutive sips. Signs of penetration or aspiration (airway response and/or wet voice after swallow) indicated a WST fail. Three swallowing performance parameters were calculated: swallow volume (mL per swallow), capacity (mL per second) and speed (time per swallow). Swallowing performance parameters were reported by age, gender and% predicted FVC. The cohort was compared with published healthy controls (Hughes and Wiles, 1996). Patients' HR, RR and SpO2 pre and post WST were obtained. Results: Thirty-three IPF patients (23 M, 10 F) completed the WST, median age 72 (52–92) years. Ten patients (10/33, 30%) were on Long Term Oxygen Therapy (LTOT). IPF patients had poorer swallow performance than the healthy people ( figure 1 ) and six patients (18%, 4 M, 2 F) failed the WST. Post-test SpO2 was higher (p=0.004). Females have lower swallow volume than males (p=0.006, mean rank difference 8.2 mL). However there was no difference for swallow capacity and speed. Conclusion: WST is an effective screening investigation in IPF, including frail patients in remote consultation. IPF patients experienced some signs of swallowing dysfunction during WST. Further work is indicated to fully explore swallowing in this vulnerable group. Reference: Hughes TA, Wiles CM. Clinical measurement of swallowing in health and in neurogenic dysphagia. Qjm 1996;89(2):109–16. Please refer to page A213 for declarations of interest related to this abstract.